Parity and non-parity determinants of Malaysia ringgit: evidence from major trading partners - Ab Razak, Nazrul Hisyam; Chee, Chong Meng; Nawawi, Noraliah (GMP Press and Printing, 2019)
The heavy slump of MYR arouses research interest in studying potential non-parity factors that affects MYR. Due to the limited empirical evidence stressed on non-parity factors, the objective of study aims to examine the effect of non-parity factors and parity factors on MYR for enriching existing literature by adding new empirical evidence. Inconsistent with the literature, the positive effects of current account balance and trade openness on MYR are found across most major trade currency pairs. It is contended that the finding may be subject to country-specific-factors requires future research endeavour.